Role of Price Fixing in Anti-Competitive Agreements under the Competition Act, 2002: Analyzing the Impact of Price Fixing on Competition (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Competition Act prohibits any enterprises or person or their association from entering into any anti-competitive agreement which causes or likely to cause an appreciable adverse effect on competition. Any such agreement, if made, shall be void. Clause (a) of section 3(3) of the Competition Act provides for the price fixing. It is the common form of anti-competitive agreements which directly or indirectly determines purchase or sale price. The aim and objective of the price fixing agreement is the elimination of competition. Such agreements are made by way of informal understanding as to prices for preventing competition and keeping the prices up. Clause (a) of section 3(3) of the Competition Act not only covers agreement between sellers but also between buyers. In India prior to the Competition Act, 2002, the practice or agreement of price fixing in concert was covered under clause (d) of section 33 of the MRTP Act.